FCSIT E-society - Lee, Jun Choi; Low, YengWoi; Yew, Poh Ling (Universiti Malaysia Sarawak, (UNIMAS), 2004)
Nowadays, the use of hypermedia system in web-based system had been a new trend of web development. Hyperwave Information Server (HIS) is one of the hypermedia systems available in the market. However, HIS is still not widely accepted in the south-east Asia region. FCSIT E-Society is an intranet system for the Faculty of Computer Science and Information technology, UNIMAS which is built on the Hyperwave Information Server 6.2. This system is a web-based community which will be implemented and used as a functional system for the member of the FCSIT UNIMAS. This report will discuss report on the background of the system development, the methodology used, the system design process, the system implementation and lastly the testing and evaluation of the developed system.